Iris images encryption based on QR code and chaotic map - Raniah Ali Mustafa; Amal Abdulbaqi Maryoosh; Dena Nadir George; Waleed Rasheed Humood (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this paper an Iris image is encrypted based on QR (quick response) code and chaotic map. The main idea of the proposed system is generating a QR code depending on the input text and then extract the features from QR code by using convolution, these features are used for key generation. After that the permuted iris image is encrypted by using generated key, after that the resulting image will be encrypts using 2D logistic map. The randomness of generated key is tested using the measures of NIST, and quality of images that encrypted in this method are tested by using security analysis tests such as PSNR, UACI, NPCR, histogram, correlation and entropy. The security analysis shows that the proposed system is secure for iris image encryption.